Phosphinothricin Acetyltransferases Identified Using In Vivo, In Vitro, and Bioinformatic Analyses - VanDrisse, Chelsey M. (Appl Environ Microbiol, 2016)
Acetylation of small molecules is widespread in nature, and in some cases, cells use this process to detoxify harmful chemicals. Streptomyces species utilize a Gcn5 N-acetyltransferase (GNAT), known as Bar, to acetylate and detoxify a self-produced toxin, phosphinothricin (PPT), a glutamate analogue. Bar homologues, such as MddA from Salmonella enterica, acetylate methionine analogues such as methionine sulfoximine (MSX) and methionine sulfone (MSO), but not PPT, even though Bar homologues are annotated as PPT acetyltransferases. S. enterica was used as a heterologous host to determine whether or not putative PPT acetyltransferases from various sources could acetylate PPT, MSX, and MSO. In vitro and in vivo analyses identified substrates acetylated by putative PPT acetyltransferases from Deinococcus radiodurans (DR_1057 and DR_1182) and Geobacillus kaustophilus (GK0593 and GK2920). In vivo, synthesis of DR_1182, GK0593, and GK2920 blocked the inhibitory effects of PPT, MSX, and MSO. In contrast, DR_1057 did not detoxify any of the above substrates. Results of in vitro studies were consistent with the in vivo results. In addition, phylogenetic analyses were used to predict the functionality of annotated PPT acetyltransferases in Burkholderia xenovorans, Bacillus subtilis, Staphylococcus aureus, Acinetobacter baylyi, and Escherichia coli. IMPORTANCE The work reported here provides an example of the use of a heterologous system for the identification of enzyme function. Many members of this superfamily of proteins do not have a known function, or it has been annotated solely on the basis of sequence homology to previously characterized enzymes. The critical role of Gcn5 N-acetyltransferases (GNATs) in the modulation of central metabolic processes, and in controlling metabolic stress, necessitates approaches that can reveal their physiological role. The combination of in vivo, in vitro, and bioinformatics approaches reported here identified GNATs that can acetylate and detoxify phosphinothricin.